2014
DOI: 10.5194/tc-8-1205-2014
|View full text |Cite
|
Sign up to set email alerts
|

The growth of sublimation crystals and surface hoar on the Antarctic plateau

Abstract: Abstract. On the Antarctic plateau, precipitation quantities are so low that the surface mass budget is for an important part determined by exchanges of water vapor between the snow surface and the atmosphere surface. At Dome C (75 • S, 123 • E), we have frequently observed the growth of crystals on the snow surface under calm sunny weather. Here we present the time variations of specific surface area (SSA) and density of these crystals. Using the detailed snow model Crocus, we conclude that the formation of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 44 publications
1
51
0
Order By: Relevance
“…The difference in optical effective particle radius between different wavelengths was largest on 5 and 6 January, when strong melting occurred and large, irregular surface snow particles with thin protrusions coexisted with smaller particles (see Table 3), causing a rough texture in the millimetre scale. This seems to be a rather common feature of the Antarctic snow surface, also observed on the high plateau (Gallet et al, 2014). At the shortest SWIR wavelengths, photons can penetrate several millimetres into the snowpack (see Fig.…”
Section: Model Discrepanciesmentioning
confidence: 99%
“…The difference in optical effective particle radius between different wavelengths was largest on 5 and 6 January, when strong melting occurred and large, irregular surface snow particles with thin protrusions coexisted with smaller particles (see Table 3), causing a rough texture in the millimetre scale. This seems to be a rather common feature of the Antarctic snow surface, also observed on the high plateau (Gallet et al, 2014). At the shortest SWIR wavelengths, photons can penetrate several millimetres into the snowpack (see Fig.…”
Section: Model Discrepanciesmentioning
confidence: 99%
“…The SSA variations observed by CORAS on 24 December 2013 are of the same order of magnitude. However, the variations observed by Gallet et al (2014b) are not symmetric to noon and their sign changes on a day-to-day scale due to the strong dependence on meteorological conditions. Even though an influence of crystal growth processes cannot be ruled out for the measurements presented here, the evident dependence on the solar zenith angle and the constant symmetry to noon of the diurnal cycle observed in the SSA retrieved from CORAS measurements strongly indicate a dominating influence of the solar zenith angle.…”
Section: Application In Cloudless Conditionsmentioning
confidence: 99%
“…To derive a more general description of the escape function, more cases and explicit BRDF measurements are needed, which is beyond the scope of this study. Furthermore, Gallet et al (2014b) observed SSA variations on a sub-daily scale using the DUFISSS instrument (DUal Frequency Integrating Sphere for Snow SSA measurements; Gallet et al, 2009) at Dome C in January 2009. They measured a drop in SSA at around noon from 40 to 33 m 2 kg −1 before the SSA increased again to 41 m 2 kg −1 at midnight.…”
Section: Application In Cloudless Conditionsmentioning
confidence: 99%
“…This leads to a maximum Pe ≈ 0.8; (3) Pe > 1 would be possible for depth hoar (Alley et al, 1990) or kinetic growth crystals, like sublimation crystals (Gallet et al, 2014, Adams andWalter, 2014) close to the surface but they were only formed under light winds conditions. According to the reported Beaufort number (in Alley et al, 1990), this will be a maximum wind speed of ≈ 2-3 m s −1 (see also Gallet et al, 2014) above the surface. In addition, they were developed in the slopes of older dunes, leading to an additional decrease of the actual wind speed (≈ 1 m s −1 ) above the layers.…”
Section: Methodsmentioning
confidence: 99%